(untitled) (Diversity Research: Journal of Analysis and Trends, 2026)
This article is devoted to the analysis of auditory perception verbs in the Uzbek and English languages, with an emphasis on the comparative coverage of the semantics and functions of these verbs in speech (grammar), and a comparative analysis of auditory perception verbs in the Uzbek and English languages